A striking common O-linked N-acetylglucosaminyl moiety between cruzipain and myosin - Acosta, Diana M (2011)
Fil: Acosta, D. M. ANLIS Dr. C. G. Malbrán. Instituto Nacional de Parasitologia Dr. Mario Fatala Chaben (INP); Argentina.